The Imprint of the War in Ford Madox Ford’s Critical Writings - Isabelle BRASME (E-REA)
Ford Madox Ford said of the year 1914 that it “seem[ed] to be cut in half” by the First World War (“Literary Portraits – LXIX”, 15). This phrase, one may argue, also largely applies to Ford’s personal timeline. Both his private life and his literary career were profoundly disrupted by the global conflict. In the early months of the First World War, Ford wrote prolifically about the future of literature and on a broader scope, of civilisation and human psychology; in his “Literary Portraits” that were published in Outlook, he showed remarkable prescience when it came to the consequences that the war would bear on the arts and on what he termed “the mind”. Yet when one examines the chronology of Ford’s non-fictional writing, and indeed of his literary work, one can sense a sharp dividing line that coincides with the moment when Ford enrolled in the British army in 1915, and was no longer a spectator from afar, but a direct witness of the unprecedented mass killing that was taking place on the front. His pre-war assertions gave way to questions; and as was the case with many other writers who took directly part in the hostilities, a decade elapsed before Ford succeeded in rendering his war experience in a novelistic form, through the Parade’s End tetralogy. This paper aims to examine Ford’s critical writing during the First World War, and to analyse the way in which he attempted to come to terms with the representational aporia that was triggered by his first-hand experience of battle. It focuses on Ford’s “Literary Portraits”; the pair of essays “A Day of Battle”, written in the Ypres Salient; “War and the Mind”, composed shortly after Ford’s return from the front; and the dedicatory letters to No More Parades, A Man Could Stand Up—, and Last Post. These allow us to explore how the impressionist technique which Ford started to theorise before the war, came to be renewed and refined in his post-war writing, trying as it does to render the inexpressible experience of the war.